Determinants of risk culture towards organisational performance (staff morale) / Nurfathinah Uzma Saharom - Saharom, Nurfathinah Uzma (Faculty of Business and Management, 2018)
A reduction or exposures to financial loss in organisation’s reserves could be the outcome of not properly managed risks in the organisation. Therefore, researcher wants to identify determinants of risk culture towards organisational performance (staff morale) of ABC Company (due to confidentiality matters, the real name of the company has been replaced to ABC Company). The objective of this research is to identify the level and correlation or relationship of determinants of risk culture: tone at the top, accountability, effective challenge and compensation with the dependent variable, organisational performance (staff morale) as well as to identify factors that affect organisational performance (staff morale). The research approach is quantitative research and self-administered questionnaire had been used as the instrument of data collection. The data was collected at a percentage of 62% or amounted to 95 respondents out of suggested sample which is 108 respondents that was derived from the total population of 153. In addition, this research use simple random sampling method as sample selection and data collected was being analysed by using Statistical Package for the Social Science (SPSS) Version 20 Software. Using SPSS, the result was then being tested by using reliability test, descriptive analysis, correlation analysis as well as multiple regression analysis. The results of this research indicated that all determinants of risk culture have shown a significant relationship with organisational performance (staff morale).